Two new species of Leptogenys from southern Brazil (Hymenoptera: Formicidae) - López-Muñoz, Román A.; Villarreal, Erick; Lattke, John E. (Zootaxa, 2018)
Two new species of ants belonging to the genus Leptogenys are described: L. academica n. sp., and L. carioca n. sp., both belonging to the crudelis group. The former species is known from the city of Curitiba while the other species occurs in montane forests of the Itatiaia Plateau. We provide descriptions based on the worker caste, images, as well as a modification of the key presently used for identifying the New World workers of Leptogenys.